Dental Photography in Practice - Gordon, P. Peter (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on dental photography in practice. Photography has always been an integral part of dentistry. Dental photography is becoming a part of the normal working day in a modern Dental Practice wherever you are in the world, from staff training to patient education and marketing. This book consists of 9 chapters, which include the DSLR body, macro lens, lighting system, setting up a DSLR for clinical use, other systems, accessories, comparison of lighting systems on teeth and models, comparison of lighting systems for faces, and standard views. The article describes the added benefits of digital dental photography over film photography, basic armamentarium for obtaining good photographs, and how digital dental photography is beneficial in the field of prosthodontics.